2016
DOI: 10.1177/1535370216662713
|View full text |Cite
|
Sign up to set email alerts
|

Biochemistry, function, and deficiency of vitamin B12 in Caenorhabditis elegans

Abstract: Caenorhabditis elegans is a nematode that has been widely used as an animal for investigation of diverse biological phenomena. Vitamin B 12 is essential for the growth of this worm, which contains two cobalamin-dependent enzymes, methylmalonyl-CoA mutase and methionine synthase. A full complement of gene homologs encoding the enzymes associated with the mammalian intercellular metabolic processes of vitamin B 12 is identified in the genome of C. elegans. However, this worm has no orthologs of the vitamin B 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 57 publications
0
27
0
1
Order By: Relevance
“…In addition, links between nutrition, DNA methylation and caste determination have been identified in social insects such as honeybees and ants 29 , 30 . In the invertebrate, Caenorhabditis elegans , B 12 is essentially required for growth and its genome contains a full complement of homologs of mammalian B 12 -related metabolic pathways 31 ; suggesting a possible role for B 12 in OCM in other invertebrate species. To increase our understanding of invertebrates, with respect to vitamin B 12 regulation and OCM, using D. magna as a model organism, we raised three main questions to test our hypothesis that environmentally induced phenotypic changes, observed in Daphnia spp., are associated with underlying epigenetic alterations to the genome: (i) Do Daphnia respond to quick dietary shifts (acute exposure) in vitamin B 12 concentration, being a key component of one-carbon metabolism and DNA methylation?…”
Section: Introductionmentioning
confidence: 99%
“…In addition, links between nutrition, DNA methylation and caste determination have been identified in social insects such as honeybees and ants 29 , 30 . In the invertebrate, Caenorhabditis elegans , B 12 is essentially required for growth and its genome contains a full complement of homologs of mammalian B 12 -related metabolic pathways 31 ; suggesting a possible role for B 12 in OCM in other invertebrate species. To increase our understanding of invertebrates, with respect to vitamin B 12 regulation and OCM, using D. magna as a model organism, we raised three main questions to test our hypothesis that environmentally induced phenotypic changes, observed in Daphnia spp., are associated with underlying epigenetic alterations to the genome: (i) Do Daphnia respond to quick dietary shifts (acute exposure) in vitamin B 12 concentration, being a key component of one-carbon metabolism and DNA methylation?…”
Section: Introductionmentioning
confidence: 99%
“…C. elegans continues to be a useful model to study B12 deficiency [55]. Worms exhibit infertility, developmental growth defects, memory impairment, and a reduced lifespan when maintained on E. coli on B12-deficient growth media [56,57].…”
Section: E Coli Acts As a Conduit For Vitamin B12 Uptakementioning
confidence: 99%
“…Supplementation with Ent was able to rescue host development on a restricted diet of Ent deficient E. coli. By using affinity purification and measuring radiolabelled 55 Fe in host mitochondria, the group demonstrated that Ent associated with the αsubunit of the host ATP synthase and that both of these components were required for the increase in levels of iron in the host mitochondria.…”
Section: Bacterial Siderophore Associates With Host To Assist Iron Upmentioning
confidence: 99%
“…To test whether the discrepancies of drp-1(lf) on the E coli K12 HT115 (B12 proficient) and E. coli B OP50 (B12 deficient) diets is caused by the B12 supply but other differences between these two E. coli strains, we supplemented the E. coli OP50 diet with pure vitamin B12 adoCbl or meCbl, which are actually interconvertible within animal cells (27,32,33). We found that either form of B12 supplementation effectively complemented the dietary B12 deficiency on E. coli OP50, as indicated by Pacdh-1::GFP expression (Figs.…”
Section: Vitamin B12 Deficiency Increases Mitochondrial Fission and Mmentioning
confidence: 99%